Taxonomic revision of the neotropical spiders of the genus idiops perty, 1833 (Araneae, idiopidae), with description of four new species - Fonseca-Ferreira, Rafael [UNESP]; Guadanucci, José Paulo Leite [UNESP]; Yamamoto, Flávio Uemori; Brescovit, Antonio Domingos (Museum National D'Histoire Naturelle, 2021)
Neotropical species of the genus Idiops Perty, 1833 are reviewed, and four new species are described from Brazil: I. duocordibus Fonseca-Ferreira, Guadanucci & Brescovit sp. nov., I. guri Fonseca-Ferreira, Guadanucci & Brescovit sp. nov., I. mocambo Fonseca-Ferreira, Guadanucci & Brescovit sp. nov. and I. sertania Fonseca-Ferreira, Guadanucci & Brescovit sp. nov. The majority of species are redescribed based on the examination of the types and extensive material. Males of I. petiti (Guérin, 1838), I. rastratus (Pickard-Cambrige, 1889), I. rohdei Karsch, 1886 and I. nilopolensis Mello-Leitão, 1923, and females of I. fuscus Perty, 1833 and I. pirassununguensis Fukami & Lucas, 2005, hitherto unknown, are described for the first time. Idiops nilopolensis, considered a nomen dubium, is revalidated. Idiops fulvipes Simon, 1889 is synonymized with I. argus Simon, 1889, and I. santaremius (Pickard-Cambrige, 1896) is synonymized with I. petiti. Neotypes are designated for Idiops fuscus, I. nilopolensis and I. siolii (Bücherl, 1953). Idiops bonapartei Hasselt, 1888 is considered species inquirendae, since the type is an immature female. Finally, an updated distribution map of Neotropical species is included. The genus now has 24 species in the Neotropical region.
Keywords: Arachnida; Domiothelina; Idiopinae; Mygalomorphae; Trapdoor spiders